2005
DOI: 10.1038/sj.npp.1300737
|View full text |Cite
|
Sign up to set email alerts
|

Cluster B Personality Disorders are Associated with Allelic Variation of Monoamine Oxidase A Activity

Abstract: Genetic variants of the monoamine oxidase A (MAOA) have been associated with aggression-, anxiety-, and addiction-related behavior in several nonclinical and clinical populations. Here, we investigated the influence of allelic variation of MAOA activity on aggressionrelated personality traits and disease risk in patients with personality disorders. Personality disorders were diagnosed with the Structured Clinical Interview of DSM-IV and were allocated to cluster A, B, and C. Personality features were assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 52 publications
(65 reference statements)
2
43
0
3
Order By: Relevance
“…Thus, carrying a short allele of the MAOA-uVNTR acted as a true and independent risk factor for later-life aggression, further adding to the risk conveyed by childhood maltreatment. Work from our group has previously shown that not only aggression, but also other domains of disruptive, outward-bound behavioral traits seem to be under partial genetic influence of MAOAuVNTR (Jacob et al, 2005). Individuals with cluster B, but not cluster C personality disorders carried short alleles more frequently, that is, MAO-A seems to play a regulatory role in the control of socially 'inappropriate' out-acting behavior.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, carrying a short allele of the MAOA-uVNTR acted as a true and independent risk factor for later-life aggression, further adding to the risk conveyed by childhood maltreatment. Work from our group has previously shown that not only aggression, but also other domains of disruptive, outward-bound behavioral traits seem to be under partial genetic influence of MAOAuVNTR (Jacob et al, 2005). Individuals with cluster B, but not cluster C personality disorders carried short alleles more frequently, that is, MAO-A seems to play a regulatory role in the control of socially 'inappropriate' out-acting behavior.…”
Section: Discussionmentioning
confidence: 86%
“…68 Thus, although there may be sizable correlations betweens behaviors and environments (e.g., a parent's antisocial behavior and their abuse of a child), correlations between genetic variants and environments are likely to be smaller because genetic variants are only weakly predictive of the behaviors that are thought to mediate the geneenvironment association. For example, the MAOA genotype is only weakly and inconsistently predictive of antisocial behavior, 59,69,70 although antisocial behavior is a relatively strong predictor of family violence. Indeed, rGEs may be small because the association between the genetic variant and the behavior that mediates the rGE is itself moderated, either behaviorally, or by other genes through the phenomenon of epistasis.…”
Section: Genotype-environment Associations: Challenges In Identifyingmentioning
confidence: 99%
“…3 The key role of MAOA in modulating monoamine turnover suggests that its gene (MAOA), located on the X chromosome (Xp11.23), is a logical candidate for investigating interindividual differences in vulnerability to psychiatric disorders, especially in males. Studies in both humans and non-human animal models have supported the involvement of MAOA in the etiology of externalizing behaviors, including impulsivity and aggression and several psychiatric disorders in which these behaviors play a role, including antisocial personality disorder (ASPD), conduct disorder (CD), attention deficit hyperactivity disorder (ADHD), and alcoholism [4][5][6][7][8][9][10] In 1993, Brunner et al 4,11 reported a Dutch family in which eight males were affected by a syndrome characterized by borderline mental retardation and impulsive behavior including impulsive aggression, arson, attempted rape, fighting, and exhibitionism The syndrome was due to a stop-codon variant in the eighth exon of MAOA leading to complete and selective deficiency of MAOA activity. This stopcodon variant has not been observed in other study populations; however, subsequent efforts led to the discovery of a common MAOA polymorphism that was shown to affect transcriptional activity [12][13][14] and that is generally assumed to result in a deficiency of MAOA in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…10 Yet several studies have failed to replicate these findings 15 and others have found that genotypes conferring high, rather than low, MAOA activity are associated with ADHD 16 and increased impulsivity, hostility, and aggression. 17 The role of MAOA in the development of antisocial behaviors has been partially clarified by studies evaluating gene -environment interaction.…”
Section: Introductionmentioning
confidence: 99%